Association of liver fibrosis with aneurysm size and mortality risk in patients undergoing open abdominal aortic aneurysm repair - Mohamad Jamalinia; Seyed Alireza Mirhosseini; Maryam Ranjbar; Kamran Bagheri Lankarani; Ahmad Hosseinzadeh (Scientific Reports)
Abstract Abdominal Aortic Aneurysm (AAA) poses a significant health risk due to its silent nature and high mortality upon rupture. The Fib-4 index, initially designed for liver fibrosis assessment, presents potential beyond its scope. This study aims to investigate the association of FIB-4 with aneurysm size and mortality risk, exploring its utility as a risk predictor for enhanced clinical management. This retrospective longitudinal research studied 141 AAA open repair surgery patients (92% male, mean age of 70 years (SD: 11.5)) from October 2016 to September 2021 for a median follow-up 35 months (IQR: 0.7 – 56.6). All-cause mortality was the primary outcome. Adjusted hazard ratios (aHR) were calculated for each Fib-4 cut-off between 1.5 and 3.25. FIB-4 cut-off range of 2.58–2.74 was associated with higher mortality risk in adjusted HR. Specifically, FIB-4 ≥ 2.67 increased mortality by 78% (aHR:1.78, 95% CI: 1.06 – 3.00). Furthermore, FIB-4 ≥ 2.67 was significantly associated with a baseline aneurysm size ≥ 8cm (aOR: 2.67, 95% CI: 1.17 – 6.09). FIB-4 was independently associated with a higher mortality risk and higher aneurysm size. These findings suggest that FIB-4 assessment in clinical practice may enhance risk profiling, aiding in more precise stratification and management strategies for AAA patients.